Fatigue-resistant electronic glass capable of being bent in multiple directions and preparation method of fatigue-resistant electronic glass
Through the two-stage treatment method of chemical thinning and local high-temperature annealing + tensile thinning, electronic glass is processed and bent groove areas are prepared on both sides, which solves the problems of existing electronic glass in scratch resistance, insufficient bending resistance and dissatisfaction with multi-directional folding requirements, and achieves higher bending fatigue life and multi-directional folding capabilities.
Patent Information
- Application Number
- CN202411844136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-15
AI Technical Summary
The existing bendable electronic glass is insufficient in terms of scratch resistance and bending resistance, and cannot meet the needs of multi-directional folding, and is prone to breaking during use.
The two-stage treatment method of chemical thinning and local high-temperature annealing + tensile thinning is adopted to process electronic glass to improve its bending resistance, and a bent groove area is prepared on both sides at the same time to achieve bidirectional folding.
It effectively avoids stress concentration at the junction of the bending area and the screen area, greatly improves the bending fatigue life of electronic glass, enhances the mechanical properties of scratch resistance and impact resistance of the display device screen, and meets the application needs of multi-directional folding.
Smart Images

Figure CN119591325A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic display devices, and in particular relates to a fatigue-resistant electronic glass that can be bent in multiple directions and a preparation method thereof. Background Art
[0002] Electronic glass generally refers to ultra-thin float glass with a thickness of less than 2mm. It refers to a type of high-tech product that can be used in the fields of electronics, microelectronics, and optoelectronics. It is mainly used to make integrated circuits and glass materials with optoelectronic, thermoelectric, acousto-optic, magneto-optic and other functional components. With the rapid development of the folding screen display market, manufacturers launch new folding screen products almost every quarter. Therefore, higher and higher requirements are put forward for the bendable electronic glass supporting folding screen display devices. It not only needs to meet optical properties such as high transmittance, but also needs to have excellent mechanical properties such as scratch resistance, drop resistance, resistance to multiple bending, and small creases.
[0003] Chinese patent CN117776519A discloses an ultra-thin flexible tempered glass and a preparation method thereof. The glass comprises, by mass percentage of oxides, 57.5-61.8% SiO2, 13.9-15.2% Al2O3, 12.1-13.2% Na2O, 6.2-7.2% MgO, 5.5-6.4% K2O, and 0.4-1.0% ZrO2. The ultimate bending radius of curvature is 4-13 mm, and the tolerable bending pressure is 400-840 MPa.
[0004] Chinese patent CN113173708A discloses a processing method for improving the bending performance of flexible glass, comprising the following steps: cutting, etching, debonding, and chemically toughening a multi-layered flexible glass to obtain a flexible glass with enhanced bending performance; wherein the multi-layered flexible glass comprises a bottom plate at the bottom layer and at least one repeating unit layer glued to the upper layer of the bottom plate, wherein the repeating unit layer comprises a flexible glass at the bottom layer and a substrate glued to the upper layer of the flexible glass, and the repeating unit layers are glued and stacked together. The final bending breakage rate is only 1-2%.
[0005] The existing bendable electronic glass is generally of uniform thickness of 20-40μm. Although it can meet the needs of flexible folding at the hinge of the mobile phone, because the entire glass is too thin, the scratch resistance and bending resistance of the front of the mobile phone screen are seriously insufficient, which greatly affects the user experience. In addition, although some scholars have proposed the concept of unequal thickness bendable electronic glass, the stress concentration in the unequal thickness joint area cannot be properly handled, which can easily lead to the breakage of the electronic glass during use. Moreover, the existing unequal thickness bendable electronic glass can only meet one-way folding and cannot be applied to the display needs of future multi-directional foldable electronic display devices. Summary of the invention
[0006] In view of the above technical problems, the present invention provides an electronic glass that can be bent in multiple directions and is fatigue-resistant, and a preparation method thereof. The electronic glass is processed by a two-stage treatment method of chemical thinning and local high-temperature annealing + stretching thinning, thereby improving the bending resistance of the electronic glass and realizing double-sided bending of the electronic glass.
[0007] In order to achieve the above object, the present invention provides a method for preparing multi-directional bendable and fatigue-resistant electronic glass, comprising the following steps: (1) Pre-cleaning: The electronic glass substrate is placed in a pre-soaking solution for cleaning, and then washed with water; (2) Film protection: Paste UV film on both sides of the pre-cleaned electronic glass sheet, leaving two non-adhesive areas on both sides; (3) Chemical thinning: Acid is sprayed on the electronic glass to chemically thin it and form etching grooves in the non-sticky area; (4) Cleaning: After removing the UV film, clean it again with pre-soaking solution; (5) Local annealing: heating the etched grooves of the electronic glass, and then performing local high-temperature annealing and stretching thinning; (6) Chemical tempering: The stretched and thinned electronic glass is placed in a tempering liquid for tempering and then cleaned.
[0008] Preferably, the electronic glass sheet in step (1) is high-aluminum electronic glass, wherein the mass fraction of aluminum is 9.7-14.8%.
[0009] Preferably, the water washing in step (1) comprises the following steps: S1: spraying with liquid medicine; S2: wind shearing + deionized water washing; S3: Ultrasonic cleaning.
[0010] Preferably, the pre-soaking solution in steps (1) and (4) is composed of 2-8% hydrofluoric acid, 7-15% auxiliary acid and 80-85% deionized water; the auxiliary acid is one or more of sulfuric acid, oxalic acid and hydrochloric acid.
[0011] Further preferably, the auxiliary acid consists of 40-60% sulfuric acid, 25-35% oxalic acid and 15-20% hydrochloric acid.
[0012] Preferably, the cleaning conditions in steps (1) and (4) are cleaning at 30-50° C. for 10-15 min.
[0013] Preferably, the width of the non-adhesive area in step (2) is 1-5 mm and the distance from the edge of the electronic glass is 50-100 mm.
[0014] Preferably, the acid solution in step (3) is composed of 5-17% hydrofluoric acid and 9-20% auxiliary acid: the auxiliary acid is one or more of sulfuric acid, oxalic acid, and nitric acid; the chemical thinning rate is 1.8-3 μm / min, and the thinning time is 100-150 min.
[0015] Further preferably, the auxiliary acid consists of 8-11% sulfuric acid, 5-6% oxalic acid, 1-3% nitric acid and deionized water.
[0016] Further preferably, the depth of the etched groove after chemical thinning is 280-300 μm, and the thickness of the glass at the etched groove after chemical thinning is 10-15% of the thickness of the unetched area.
[0017] Preferably, the UV film is removed in step (4) by irradiating with ultraviolet light for 1-2 minutes.
[0018] Preferably, the local high temperature annealing condition in step (5) is 400-600° C. for 3-8 min; and the tensile force for the stretching and thinning is 3-6N.
[0019] Preferably, the tempering temperature in step (6) is 390-450° C., and the tempering time is 1.5-3 h.
[0020] The present invention also provides a fatigue-resistant electronic glass that can be bent in multiple directions. The A and B surfaces of the fatigue-resistant electronic glass that can be bent in multiple directions contain symmetrical bending groove areas.
[0021] Preferably, the width of the bending groove area is 1-5 mm, the depth is 280-300 μm, the bidirectional bending radius is 0.8-1.3 mm, and the number of the bending groove areas is ≥2.
[0022] The beneficial effects of the present invention are: 1. The electronic glass is processed by a two-stage treatment method of chemical thinning and local high-temperature annealing + stretching thinning, which effectively avoids stress concentration at the junction of the bending area and the screen area, greatly improves the bending fatigue life of the electronic glass, and enhances the mechanical properties of the display device screen, such as scratch resistance and impact resistance.
[0023] 2. The bending groove areas are prepared on both sides of the electronic glass at the same time, which realizes the bidirectional folding of the electronic glass, broadens the application scope of the multi-directional folding of foldable electronic display devices, and can meet the diversified development needs of electronic display devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of UV film coating.
[0025] Figure 2 This is a schematic structural diagram of the multi-directionally bendable and fatigue-resistant electronic glass prepared in Example 1.
[0026] In the figure, 1 is the electronic glass A surface, 2 is the electronic glass B surface, 3 is the bending groove area, 4 is the electronic glass, 5 is the non-adhesive area, and 6 is the UV film. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be understood as limiting the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims. Any modification or replacement made by those skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.
[0028] Example 1 (1) Take a high-aluminum ultra-thin electronic glass original sheet with a size of 100×180×0.33 mm, place it in a pre-soaking solution and soak it at 40°C for 10 min; the pre-soaking solution includes 5% hydrofluoric acid, 7% auxiliary acid, and the remainder is deionized water; the auxiliary acid is composed of 50% sulfuric acid, 30% oxalic acid, and 20% hydrochloric acid; (2) Cleaning the electronic glass substrate after cleaning with the pre-soaking solution, the specific steps include: S1: Chemical solution spraying: The chemical solution is composed of 0.05% sodium hydroxide and deionized water; the spraying method is vertical spraying from the top; the spraying flow rate is 500mL / min; the spraying time is 30-50s; S2: wind shearing + deionized water washing: the wind speed during wind shearing is 3m / s, the water flow rate of deionized water washing is 10L / min, and the total treatment time is 10s); S3: Ultrasonic cleaning: frequency 80kHz, time 45s); S4: Circulating water washing: ultrapure water is used for circulating water washing, wherein the spraying method is vertical spraying from the top, the single washing time is 45s, and the number of cycles is 5 times; S5: High temperature air knife drying: temperature 50°C; wind speed 5m / s; processing time 55s) (3) UV film is applied to both sides of the original electronic glass sheet, and two non-adhesive areas are left on both sides. The width of the non-adhesive areas is 1 mm and the distance from both sides of the original electronic glass sheet is 50 mm. (4) The electronic glass substrate was chemically thinned on both sides by top spray chemical thinning method, and symmetrical etching grooves with a depth of 280 μm were formed on both sides of the glass, wherein the thinning rate was 2 μm / min; wherein the acid solution formula for chemical thinning was: 5% hydrofluoric acid, 10% sulfuric acid, and the balance was deionized water; (5) Expose the double-sided chemically thinned electronic glass substrate to a UV curing lamp for 1 min to remove the UV film, and repeat the cleaning step (2); (6) locally heating the electronic glass original sheet obtained in step (5) to 500° C. and keeping the temperature for 5 min. At the same time, applying a tensile force of 5 N to both sides of the electronic glass original sheet for 5 min to perform local high-temperature annealing; wherein the local heating rate is 10° C. / min and the local heating is limited to the etching groove; (7) The electronic glass original sheet obtained in step (6) is placed in a tempering liquid at 390° C. for 1.5 hours, and step (2) is repeated for cleaning to obtain a multi-directional bendable and fatigue-resistant electronic glass, wherein the formula of the tempering liquid is potassium nitrate molten salt.
[0029] Example 2 The method and steps are the same as in Example 1, except that some preparation conditions are changed as follows: The formula of the pre-soaking solution in step (1) is changed to 6% hydrofluoric acid, 7% auxiliary acid, and the balance is deionized water. The soaking temperature is changed to 30°C and the soaking time is changed to 15 minutes. The auxiliary acid is composed of 60% sulfuric acid, 25% oxalic acid, and 15% hydrochloric acid. The width of the non-adhesive area in step (3) was changed to 3 mm; The thinning rate in step (4) is 2.2 μm / min, the depth of the etching groove is 290 μm, and the formula of the acid solution during chemical thinning is 5% hydrofluoric acid, 20% auxiliary acid, and the balance is deionized water; wherein the auxiliary acid is composed of 8% sulfuric acid, 5% oxalic acid, 1% nitric acid and deionized water; The temperature in step (6) was changed to 400°C, the holding time was changed to 8 min, and the tension was changed to 3 N; The tempering temperature in step (7) was changed to 420°C and the holding time was changed to 2 h.
[0030] Example 3 The method and steps are the same as in Example 1, except that some preparation conditions are changed as follows: The formula of the pre-soaking solution in step (1) is changed to 7% hydrofluoric acid, 10% auxiliary acid, and the balance is deionized water. The soaking temperature is changed to 50°C and the soaking time is changed to 12 minutes. The auxiliary acid is composed of 40% sulfuric acid, 35% oxalic acid, and 15% hydrochloric acid. The width of the non-adhesive area in step (3) was changed to 5 mm; The thinning rate in step (4) is 2.5 μm / min, the depth of the etching groove is 300 μm, and the formula of the acid solution during chemical thinning is composed of 17% hydrofluoric acid, 9% auxiliary acid and deionized water; wherein the auxiliary acid is composed of 11% sulfuric acid, 6% oxalic acid, 3% nitric acid and deionized water; The temperature in step (6) was changed to 600°C, the holding time was changed to 3 min, and the tension was changed to 6 N; The tempering temperature in step (7) was changed to 450°C and the holding time was changed to 3 h.
[0031] Comparative Example 1 The method and steps are the same as those in Example 1, wherein the non-adhesive area in step (3) is changed to two strips on one side, and step (6) is omitted, thereby preparing electronic glass.
[0032] Comparative Example 2 The method and steps are the same as those in Example 1, wherein the non-adhesive area in step (3) is changed to two strips on one side to prepare electronic glass.
[0033] Comparative Example 3 The method and steps are the same as those in Example 1, except that step (6) is omitted, and electronic glass is prepared.
[0034] Comparative Example 4 The method and steps are the same as those in Example 1, except that the stretching and thinning in step (6) is omitted to prepare electronic glass.
[0035] Comparative Example 5 The method and steps are the same as those in Example 1, except that step (3) is omitted and UV film coating is not performed to prepare electronic glass.
[0036] Result detection: The electronic glass prepared in the above embodiments and comparative examples was taken, and its groove morphology was detected by visual inspection, its bending performance was detected by a bending tester, its scratch resistance was detected by a scratch method (refer to GB / T 39815-2021 (Ultra-thin glass scratch resistance test method), its impact resistance was detected by a pen drop method (refer to GB / T 39814-2021 (Ultra-thin glass impact strength test method), and the stress performance of the bending area and the screen area was detected by referring to GB / T 44752-2024 (Flexible glass bending fatigue test method). The results are shown in the following table:
[0037] It can be seen from the data in the table that the electronic glass that has undergone a two-stage process of chemical thinning and physical annealing thinning can meet the needs of multi-directional folding. Compared with the control example, the stress concentration at the edge of the groove is greatly reduced, the bending radius is smaller, and its fatigue resistance is also superior.
Claims
1. A method for preparing a multi-directional bendable and fatigue-resistant electronic glass, characterized in that: The steps include: (1) Pre-cleaning: The original electronic glass sheet is placed in a pre-soaking solution for cleaning, and then washed with water; (2) Film protection: Paste UV film on both sides of the pre-cleaned electronic glass sheet, leaving two non-adhesive areas on both sides; (3) Chemical thinning: Acid is sprayed on the electronic glass to chemically thin it and form etching grooves in the non-sticky area; (4) Cleaning: After removing the UV film, clean it again with pre-soaking solution; (5) Local annealing: heating the etched grooves of the electronic glass, and then performing local high-temperature annealing and stretching thinning; (6) Chemical tempering: The stretched and thinned electronic glass is placed in a tempering liquid for tempering and then cleaned.
2. The preparation method according to claim 1, characterized in that: The pre-soaking solution in steps (1) and (4) is composed of 2-8% hydrofluoric acid, 7-15% auxiliary acid and 80-85% deionized water; the auxiliary acid is one or more of sulfuric acid, oxalic acid and hydrochloric acid.
3. The preparation method according to claim 1, characterized in that: The cleaning conditions in steps (1) and (4) are cleaning at 30-50°C for 10-15 minutes.
4. The preparation method according to claim 1, characterized in that: The width of the non-adhesive area in step (2) is 1-5 mm and the distance from the edge of the electronic glass is 50-100 mm.
5. The preparation method according to claim 1, characterized in that: The acid solution in step (3) is composed of 5-17% hydrofluoric acid and 9-20% auxiliary acid: the auxiliary acid is one or more of sulfuric acid, oxalic acid, and nitric acid. The chemical thinning rate is 1.8-3 μm / min, and the thinning time is 100-150 min.
6. The preparation method according to claim 1, characterized in that: The UV film is removed in step (4) by irradiating with ultraviolet light for 1-2 minutes.
7. The preparation method according to claim 1, characterized in that: The local high temperature annealing condition in step (5) is 400-600° C. for 3-8 min; the tensile force for the stretching and thinning is 3-6N.
8. The preparation method according to claim 1, characterized in that: The tempering temperature in step (6) is 390-450°C, and the tempering time is 1.5-3h.
9. An electronic glass that is multi-directionally bendable and fatigue-resistant, prepared according to the preparation method according to any one of claims 1 to 8, characterized in that: The A and B surfaces of the multi-directionally bendable and fatigue-resistant electronic glass contain symmetrical bending groove areas.
10. The multi-directional bendable and fatigue-resistant electronic glass according to claim 9, characterized in that: The width of the bending groove area is 1-5 mm, the depth is 280-300 μm, the bidirectional bending radius is 0.8-1.3 mm, and the number of the bending groove areas is ≥2.
Citation Information
Patent Citations
Processing method for improving bending performance of flexible glass
CN113173708A
Ultrathin flexible tempered glass and preparation method thereof
CN117776519A
Manufacturing method and structure for improving bendability of ultrathin glass mobile phone cover plate
CN111453984A
Slotted ultrathin glass and processing method thereof
CN117383834A
Bendable ultra-thin glass and preparation method thereof
CN117865500A